Usage of Mitogen-Activated Protein Kinase Small Molecule Inhibitors: More Than Just Inhibition! - Meurer, Steffen K.; Weiskirchen, Ralf (Frontiers in Pharmacology, 2018)
We have identified a phenomenon occurring in the usage of proposed “specific” Mitogen-activated protein kinases inhibitors. We found that especially inhibitors of p38 potentiate the activation of other MAPKs in various cell types. This finding will have tremendous impact on the interpretation of all former studies using MAPK inhibitors.